Effect of Salinity and Harvesting on Population Dynamics and Composition of Natural Copepods Fed with Fermented Bran - Ourgern, Doungtip; Muthuwan, Vorathep; Fakrajung , Siraprapa; Sakpraseat, Chonticha (Burapha Science Journal, 2026)
An experiment was conducted to study the effect of 3 different salinity levels (28, 30, 32 ppt) and frequency of harvesting at the end (30 days.) and double harvesting on days 12 and 30 (the end) fed with fermented bran as concentration 150 ppm first feeding only. Factorial design in eighteen of 10-liter plastic tanks for 30 days. The results showed that responded copepods by increasing the maximum copepod density was (mean±SE) 3.1±0.3 and 2.8±0.3 ind./mL on day 2 before the reversal at high density (Mean±SE) 2.8±0.4 and 1.0±0.2 ind./ mL in day 10 at salinity 28 ppt in both 2 harvests, respectively. Different (p<0.01) at high salinity 30 and 32 ppt to copepod density was (mean±SE) 1.3±0.1 and 0.9-0.1 ind./mL at 12-14 days before increasing at the same approach. Half-harvested copepods at 12 days did not affect of density copepods in the end. Most types of copepod were order calanoid, cyclopoid and harpacticoid copepod (Percent 59.1±0.1, 27.9, 12.5) and the stage were nauplii, adult, copepodite and adult with eggs (Percent 55.8±4.8, 24.5±3.4, 19.2±2.1, 0.5±0.2), respectively. Concluded there were copepods prefer salinity of 28 ppt and double harvesting increased the production of copepods.